PREVALENCE AGREEMENT AND PROGNOSTIC VALUE OF EWGSOP AND FNIH SARCOPENIA DEFINITION: THE GLISTEN STUDY. (11th November 2018) - Volpato, S; Bianchi, L; Landi, F
Abstract: Sarcopenia is common among hospitalized older people. The European Working Group on Sarcopenia in Older People (EWGSOP) and the Foundation for the National Institutes of Health (FNIH) Sarcopenia Project proposed similar diagnostic criteria but, although measures of muscle mass and muscle strength overlap, the operational definition differ. Using data from a sample of hospitalized older people, we assessed prevalence agreement of the two definitions and we compared the predictive value for disability, re-hospitalization, and mortality risk in the year following hospital discharge. Data are from the GLISTEN Study, a multicenter observational study of 611 older adults (mean age 80.6 ± 6.6 years, female 51.2%) admitted to 12 Italian hospitals. Appendicular skeletal muscle mass assessed by bioimpendance was standardized for height or BMI according to EWGSOP and FNIH definition respectively. Analyses were performed using Cohen's kappa, logistic regression, Cox models and negative binomial regression analyses. Sarcopenia prevalence was 24% and 36% using the FNIH and EWGSOP definitions, respectively, with a low classification's agreement (Kappa Statistic: 0.12). BMI was directly associated with sarcopenia according to FNIH definition and inversely associated with EWGSOP classification. In logistic regression analysis, only FNIH definition was associated with severe disability. Cox models showed that, after multiple adjustment, FNIH but not EWGSOP sarcopenia classification predicted one-year mortality. Negative binomial regression analyses shown a significant higher hospitalization rate for FNIH definition. Agreement between EWGSOP and FNIH sarcopenia definitions is poor. Our findings suggest that FNIH classification might have better prognostic value for important clinical endpoints.